Program Milk for Children: a public policy to encourage local production and food and nutritional security - Bazotti, Angelita; Conti, Irio Luiz; Finokiet, Manuela (Universidade Federal Rural do Rio de Janeiro, 2016)
Discussions about food long take up space in the political and academic circles. But, before the focus of the discussions fell on hunger and food access, now turns to alternative foods, food and nutrition security. This article presents the Milk for Children Program, analyzing it as a public policy that has its place of creation and implementation in a notion’s state more permeable to local development. The program seeks to provide access to quality food, to boost local development. Noteworthy is the incentive for local production and its importance to sustainable development, but keeping the criticism of localism. This is not to qualify, a priori, products as good only because they come from local production. Rather than hold up the issues of scale, public planners need to stick to the goal of politics. The program strengthens the small producers and small dairy. However, to ensure children have the right to access to milk, also resort to large companies to ensure supply. Such initiatives demonstrate the growing concern of the government actions with local development and encouraging producers to remain on rural areas producing food for the food and nutritional security.